2020
DOI: 10.2514/1.c035602
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelastics Flight Dynamics Coupling Effects of the Semi-Aeroelastic Hinge Device

Abstract: A recent consideration in aircraft design is the use of folding wing-tips with the aim of enabling higher aspect ratio aircraft with less induced drag, but also meeting airport gate limitations. This study investigates the impact of floating folding wing-tips on the aircraft flight dynamics. It is found that a floating wing-tips aircraft has similar handling qualities with respect to an aircraft with no wing extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…The present modeling of coupled aeroelasticity and flight dynamics is based on the formulation in Refs. [11,12], in which the rigid body degrees of freedom are associated with a set of pratical mean axes (PMAs) and the linearized structural dynamics is described as a combination of unconstrained aircraft mode shapes in the PMAs coordinate system that simplifies the inertial coupling description. The PMAs are featured by having the origin coinciding with the instantaneous center of mass of the aircraft, and the orientation of the principal axes remains constant in the deformed configuration.…”
Section: Integration Of Sloshing Rom Into a Flexible Aircraft Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The present modeling of coupled aeroelasticity and flight dynamics is based on the formulation in Refs. [11,12], in which the rigid body degrees of freedom are associated with a set of pratical mean axes (PMAs) and the linearized structural dynamics is described as a combination of unconstrained aircraft mode shapes in the PMAs coordinate system that simplifies the inertial coupling description. The PMAs are featured by having the origin coinciding with the instantaneous center of mass of the aircraft, and the orientation of the principal axes remains constant in the deformed configuration.…”
Section: Integration Of Sloshing Rom Into a Flexible Aircraft Modelmentioning
confidence: 99%
“…The linearized relation between Δ in Eq. (12) and Δ is expressed as with which allows to highlight the link between the variables expressed in the PMAs and those defined in the inertial reference system (being * 1 a square matrix with dimension ( 9 + N e )).…”
Section: Integration Of Sloshing Rom Into a Flexible Aircraft Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…For the larger wingtips, there is an increase in the roll damping coefficient due to both downward and upward deflections by an amplitude of 4 and 2%, respectively, when compared with the baseline aircraft at similar flight conditions. Similarly, Castrichini et al [13] studied the impact of the semiaeroelastic hinge (SAH) on the flight dynamics of a narrow-body transport aircraft. They concluded that an aircraft equipped with floating wingtips has similar handling qualities with respect to an aircraft with no wing extension.…”
mentioning
confidence: 99%